2012
DOI: 10.1016/j.jpeds.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Youth with Medically Unexplained Chest Pain versus Innocent Heart Murmur

Abstract: Objective To examine prevalence of DSM-IV psychiatric disorders in youth with chest pain compared with a control sample with innocent heart murmur. Study design We assessed youth ages 8–17 years who were evaluated in cardiology settings for medically unexplained chest pain (N=100) or innocent heart murmur (N=80). We conducted semi-structured interviews and assessed medical history, quality of life, and disability. Results Youth with chest pain had a higher prevalence of psychiatric disorders compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Another study in children and adolescents with unexplained chest pain, who presented to paediatric emergency department, showed high rates of psychopathology (27 of 32 children, 84%) using Diagnostic Statistical Manual of Mental Disorders, Fourth Edition and a large percentage of the sample (81%) had anxiety disorder. 21 Finding is also consistent with the result of other study by Lipsitz et al 22 in youngsters with non-cardiac chest pain. They found a higher prevalence of Diagnostic Statistical Manual of Mental Disorders, Fourth Edition, psychiatric disorders in children and adolescents with medically unexplained chest pain compared to a control sample with innocent heart murmur (74% versus 38%), and anxiety was again found most common (70%) in psychiatric disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study in children and adolescents with unexplained chest pain, who presented to paediatric emergency department, showed high rates of psychopathology (27 of 32 children, 84%) using Diagnostic Statistical Manual of Mental Disorders, Fourth Edition and a large percentage of the sample (81%) had anxiety disorder. 21 Finding is also consistent with the result of other study by Lipsitz et al 22 in youngsters with non-cardiac chest pain. They found a higher prevalence of Diagnostic Statistical Manual of Mental Disorders, Fourth Edition, psychiatric disorders in children and adolescents with medically unexplained chest pain compared to a control sample with innocent heart murmur (74% versus 38%), and anxiety was again found most common (70%) in psychiatric disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Lipsitz et al 11 showed that youngsters with non-cardiac chest pain and benign heart murmur had similar mean scores on Child Depression Inventory depressive symptoms, and depression rates (11% of non-cardiac chest pain and 7% of benign heart murmur groups) did not differ across the groups. Another study of Lipsitz et al 22 between children and adolescents with medically unexplained chest pain and innocent heart murmur showed higher prevalence (9% versus 0) of any depression in the chest pain group using Diagnostic Statistical Manual of Mental Disorders, Fourth Edition: Child and Parent version.…”
Section: Discussionmentioning
confidence: 96%
“…Uncontrolled studies that used a standardized psychiatric interview to assess children and adolescents with unexplained chest pain found that 81% of those presenting to a specialty cardiac clinic and 56% of those presenting to the emergency department met criteria for diagnosis of an anxiety disorder (Lipsitz et al., 2005, 2010). In a subsequent controlled study, psychiatric disorder was significantly more likely in youth presenting with chest pain in a specialty cardiac setting than in controls, with 74% of the chest pain group meeting criteria for a psychiatric disorder, with the most prevalent diagnosis being that of an anxiety disorder (Lipsitz et al., 2012).…”
mentioning
confidence: 95%
“…Tunaoglu et al 14 showed 75% psychiatric disorder and 21% anxiety symptoms in 74 youngsters with noncardiac chest pain in a paediatric cardiology service, based on the Diagnostic Statistical Manual of Mental Disorders, Third Edition-R. Another study in children and adolescents with noncardiac chest pain who were admitted to a paediatric emergency department showed high rates of psychopathology (27 of 32 children, 84%) using the Diagnostic Statistical Manual of Mental Disorders, Fourth Edition, and a large percentage of the sample (81%) had anxiety disorder. 20 Lipsitz et al 21 found a higher prevalence of Diagnostic Statistical Manual of Mental Disorders, Fourth Edition psychiatric disorders in children and adolescents with non-cardiac chest pain than in a control sample with innocent heart murmur (74% versus 38%), and anxiety was again found to be the most common (70%) among psychiatric disorders. Another study by Lipsitz et al showed that youngsters who had been diagnosed several years earlier with non-cardiac chest pain reported more current symptoms of anxiety, anxiety sensitivity, and physiological arousal than children with benign murmurs.…”
Section: Discussionmentioning
confidence: 98%